Intimate Class Acts : Friendship and Desire in Indian and Pakistani Women's Fiction - Maryam Mirza (New Delhi Oxford University Press, 2016)
In this scholarly work, Maryam Mirza examines ten novels in English by women writers from the Indian subcontinent. She explores the role of power and desire, and of emotional and physical intimacy in cross-class relations. Striking similarities in how gendered and classed identities are lived in India and Pakistan are revealed in this text
Include Bibliography and Index
Keywords: Indic fiction (English)--Women authors -- Desire in literature -- Friendship in literature